Healthy Way Of Eating Food - Ayurvedic Guidelines - Gupta, Anamika; Rath, Vd Sudipta Kumar (International Research Journal of Ayurveda & Yoga, 2020)
Introduction - Health is an outcome of proper food (input), proper digestion and metabolism (throughout) and proper utilization and excretion (output). Currently a vast body of information on the nutritional requirement is available and accordingly guidelines are also widely available for better health. It is interesting to note that despite this information, we are not able to achieve the goals of healthy diet even if amongst the population who are using these healthy diets. The reason for this, as described in Ayurveda is the lack of proper knowledge of individualized dietary guidelines (based on Prakriti, Desha and Kala) and the rules pertaining to consumption of diet (Ahara vidhi visheshayatan). Therefore, it is pertinent to review the whole gamut of guidelines about food and way to consume food as described in Ayurveda so as to improve the existing dietary guidelines. Materials and methods- This study comprises collection and critical review of literature in the ancient classical texts, scientific journals, research papers, dissertation etc. Observations - Ayurveda describes that the dietary requirements are different based on the Prakriti, place of origin and residence and time of consumption of food. The concept is alike the personalized medicine concept of modern medicine and can be termed as Personalized Diet. Further, Ayurveda lays a lot of importance on how the food has to be consumed for optimum utilization. Charaka states that there are eight important factors which can lead to proper utilization of consumed diet or otherwise. These include the nature of the food, the processing and its effect on the diet, etc. Awry consideration of these in the pursuit of taste can lead to long term harmful effect on the user. Discussion and conclusion – It is quite evident that a more holistic dietary guideline is prescribed in Ayurveda in comparison to the present trend of dietary guideline. Following this holistic individual healthy way of eating food is the key to achieve optimum health.